Phosphorylation-dependent ubiquitylation and degradation of androgen receptor by Akt require Mdm2 E3 ligase - Lin, Hui-Kuan (Oxford University Press, 2002)
The androgen receptor (AR) controls several biological functions including prostate cell growth and apoptosis. However, the mechanism by which AR maintains its stability to function properly remains largely unknown. Here we show that Akt and Mdm2 form a complex with AR and promote phosphorylation-dependent AR ubiquitylation, resulting in AR degradation by the proteasome. The effect of Akt on AR ubiquitylation and degradation is markedly impaired in a Mdm2-null cell line compared with the wild-type cell line, suggesting that Mdm2 is involved in Akt-mediated AR ubiquitylation and degradation. Furthermore, we demonstrate that the E3 ligase activity of Mdm2 and phosphorylation of Mdm2 by Akt are essential for Mdm2 to affect AR ubiquitylation and degradation. These results suggest that phosphorylation-dependent AR ubiquitylation and degradation by Akt require the involvement of Mdm2 E3 ligase activity, a novel mechanism that provides insight into how AR is targeted for degradation.